Simple Febrile Seizure: The Role of Serum Sodium Levels in Prediction of Seizure Recurrence during the First 24 Hours - Heydarian, F.; Ashrafzadeh, F.; Kam, S. (Iranian Journal of Child Neurology, 2009)
Objective Simple febrile seizures are the most common form of childhood seizures,often recurring within the first twenty-four hours. This study was conducted to determine the probable role of low serum sodium levels in predicting seizure recurrence in febrile children. Materials & Methods For the study, 226 patients with seizures, aged between 6 months to 5 years, were divided into 3 groups of simple febrile seizure, simple febrile seizure with recurrence, and the control group of afebrile patients with seizures. For all groups, serum sodium levels were evaluated. Results The mean age of our cases, predominantly male, was 22 months. No significant difference was observed in the serum sodium levels between the simple febrile seizure and the simple febrile seizure with recurrence groups (P value 0.465); however a significant relative hyponatremia was observed in the simple febrile seizure group as compared to the afebrile seizure control group (P value: 0.016). Conclusion Based on the findings, although serum sodium levels cannot assist in prediction of recurrence of simple febrile seizures in children, relative hyponatremia may predispose the febrile child to occurrence of simple febrile seizure.